Could the Digital Option Work for a Book Market under Stress? The Case of Greek Publishers. - Karakatsouli, Anna (International Journal of the Book, 2018)
In 2009, five major Greek publishers launched their first e-books along with specific reading devices introducing digital publishing to the Greek public almost twenty years after its appearance in the international scene. This first attempt did not lead to the establishment of an e-book market. E-readers were expensive and the fact that the Greek economy was being brought to a standstill at the same moment stopped all developments in that direction. Nine years later, e-books are still an infant industry in Greece with only a marginal part of 1 percent in publishers' turnovers. Greek publishers, however, turn to the digital environment pursuing innovative actions to reach new readers, offer novel possibilities to writers, and take advantage of social networks for marketing purposes. This article shall examine digital start-ups and recent initiatives in the Greek e-book market in order to evaluate their scope and effectiveness in conditions of economic depression and to discuss the current reception of e-books among Greek readers.